High penetrance of inferior vena cava system atresia in severe thrombophilia caused by homozygous antithrombin Budapest 3 variant: Description of a new syndrome. Issue 11 (12th August 2021) - de la Morena‐Barrio, María E.; Gindele, Réka; Bravo‐Pérez, Carlos; Ilonczai, Péter; Zuazu, Isabel; Speker, Marianna; Oláh, Zsolt; Rodríguez‐Sevilla, Juan J.; Entrena, Laura; Infante, Maria S.; de la Morena‐Barrio, Belén; García, José M.; et al.
Abstract: Atresia of inferior vena cava (IVC) is a rare congenital malformation associated with high risk of venous thrombosis that still has unknown etiology, although intrauterine IVC thrombosis has been suggested to be involved. The identification of IVC atresia in a case with early idiopathic venous thrombosis and antithrombin deficiency caused by the homozygous SERPINC1 c.391C > T variant ( p.Leu131Phe ; antithrombin Budapest 3) encouraged us to evaluate the role of this severe thrombophilia in this vascular abnormality. We have done a cross‐sectional study in previously identified cohorts of patients homozygous for the Budapest 3 variant ( N = 61) selected from 1118 patients with congenital antithrombin deficiency identified in two different populations: Spain ( N = 692) and Hungary ( N = 426). Image analysis included computed tomography and phlebography. Atresia of the IVC system was observed in 17/24 cases (70.8%, 95% confidence interval [CI]: 48.9%–87.3%) homozygous for antithrombin Budapest 3 with available computed tomography (5/8 and 12/16 in the Spanish and Hungarian cohorts, respectively), 16 had an absence of infrarenal IVC and one had atresia of the left common iliac vein. All cases with vascular defects had compensatory mechanisms, azygos‐hemiazygos continuation or double IVC, and seven also had other congenital anomalies. Short tandem repeat analysis supported the specific association of the IVC system atresia with SERPINC1 . We show the first evidence of the association of a severe thrombophilia with IVC system atresia, supporting the possibility that a thrombosis in the developing fetal vessels is the reason for this anomaly. Our hypothesis‐generating results encourage further studies to investigate severe thrombophilic states in patients with atresia of IVC.